O Lugar da integração latino-americana em discursos de Lula e Chávez. - Alexius, Sofia Cristina (2011)
The purpose of this project is to analyze president Lula s and Chávez s political speeches, relying on the theoretical support of the Rhetorical Discourse Theory (TRD), which organizes the argumentative discourse in three dimensions: rationalizing, aesthetics and politics. Technical, legitimating and sensitizing arguments are the objects of the analysis (rationalizing dimension), as well as language features (aesthetic dimension) and interaction between the subjects of discourse (political dimension) used by the presidents of Brazil and Venezuela when they give speeches on the integration process in Latin America. The research material consists of 10 speeches, 05 of each president, delivered between the years 2008 and 2010. The analysis shows that the concept of integration is highlighted in the defense of three main theses, supported by both presidents: a) integration is required; b) the integration is already happening; c) the need for integration.